2011
DOI: 10.1242/dmm.006841
|View full text |Cite
|
Sign up to set email alerts
|

A translational continuum of model systems for evaluating treatment strategies in Alzheimer’s disease: isradipine as a candidate drug

Abstract: SUMMARYA growing body of evidence supports the ‘calcium hypothesis’ of Alzheimer’s disease (AD), which postulates that a variety of insults might disrupt the homeostatic regulation of neuronal calcium (Ca2+) in the brain, resulting in the progressive symptoms that typify the disease. However, despite ongoing efforts to develop new methods for testing therapeutic compounds that might be beneficial in AD, no single bioassay permits both rapid screening and in vivo validation of candidate drugs that target specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 112 publications
0
36
0
Order By: Relevance
“…Treatment with Aβ 1-42 induces concentration-dependent perturbations in the extent of migration and outgrowth of enteric nervous system. A simultaneous treatment with isradipine prevents the deleterious effects of Aβ [93]. Our studies further show that subcutaneous administration of isradipine (3 μg/g/day; 60-day release) to 3xTgAD mice was well-tolerated and isradipine became available to the brain [29, 93].…”
Section: Calcium Channel Blockers To Break the Nexus Of Toxicitymentioning
confidence: 69%
See 2 more Smart Citations
“…Treatment with Aβ 1-42 induces concentration-dependent perturbations in the extent of migration and outgrowth of enteric nervous system. A simultaneous treatment with isradipine prevents the deleterious effects of Aβ [93]. Our studies further show that subcutaneous administration of isradipine (3 μg/g/day; 60-day release) to 3xTgAD mice was well-tolerated and isradipine became available to the brain [29, 93].…”
Section: Calcium Channel Blockers To Break the Nexus Of Toxicitymentioning
confidence: 69%
“…We also tested isradipine for its neuroprotective functions in four evolutionarily divergent species including models for AD: human neuroblastoma/MC65 cells, transgenic Drosophila , Monduca , and 3xTg-AD mice [93]. In transgenic Drosophila model, 250 μM isradipine increased the survival of flies from 6.5% to 12% (p<0.5) against APP 695 toxicity [93].…”
Section: Calcium Channel Blockers To Break the Nexus Of Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that nimodipine can prevent Aβ-mediated neurotoxicity was confirmed in cortical neurons by use of a more relevant, stable oligomeric Aβ preparation (Fu et al, 2006). Other calcium antagonists (verapamil, diltiazem and isradipine) all dose dependently protected Aβ-induced cellular degeneration in cultured cells (Anekonda et al, 2011;Copenhaver et al, 2011), strengthening the conclusion that L-type channels may mediate the toxic effect. Using calciumsensitive dyes, several groups showed that Aβ25-35 increases intracellular calcium levels, and different classical calcium antagonists prevent this increase in vitro (Silei et al, 1999;Yagami et al, 2002;Fu et al, 2006).…”
Section: Aβ Modulates Vgccsmentioning
confidence: 79%
“…57 Isradipine limits the neurotoxic damage caused by A␤ in cell cultures and animal models. 58 Nimodipine, despite its effects on LTCC, stimulates A␤ secretion through another mechanism. A CC study demonstrated lower risk of PD among CCA users, while another CC study and 2 prospective studies found no associations.…”
Section: Calcium Channel Antagonistsmentioning
confidence: 99%